Daily Meditation Practice for Managing Glaucoma Patients' Attitudes and Acceptance. Issue 9 (12th July 2022) - Brogan, Kerr; Bigirimana, Deus; Wightman, Antony; Green, Catherine; Martin, Keith R.
Abstract : Précis: Overall, 63% of glaucoma patients agreed to 45-60 minutes of daily meditation. Predictors of accepting meditation included previous meditation practice, a diagnosis of glaucoma <1 year, and having a marital status of "single". Purpose: To explore patients' acceptance and barriers towards 45-60 minutes daily meditation for glaucoma management and to identify glaucoma patients with higher perceived stress levels who may benefit more from meditation practice. Methods: Glaucoma patients attending the Royal Victorian Eye and Ear Hospital, Melbourne, Australia outpatient department were invited to complete a patient survey. This survey explored if patients would agree to 45-60 minutes of daily meditation and included the Determinants of Meditation Practice Inventory and Perceived Stress Scale questionnaires. Questionnaire scores were compared across participants' clinical and demographic characteristics using Student t test, ANOVA, and multiple-linear-regression analysis. Results: Of the 123 eligible patients screened, 100 completed the survey (81.3%). Sixty-three (63%) patients would agree to 45-60 minutes of daily meditation if advised by their doctor. Univariate analysis showed increased acceptance of meditation (lower Determinants of Meditation Practice Inventory scores) to be associated with agreeing to meditate 45-60 minutes daily ( P =0.002), currently or previously practicing meditation ( P =0.006 and P =0.0004 respectively), and having a marital status as "single" ( P =0.02). Multivariate regression analysis showed previous meditation practice and a glaucoma diagnosis of <1 year to be predictive of accepting meditation ( P =0.01 and P =0.03 respectively). There were no predictive factors of Perceived Stress Scale scores. Conclusion: Given the high acceptance rate of 45-60 minutes daily meditation (63% of glaucoma patients sampled), this may be recommended for the benefit of patients. Patients who have previously meditated, have a relatively new diagnosis of glaucoma, and are single (marital status) were more accepting of meditation practice.